Supervisi dalam Perspektif Al-Qur’an dan Hadis : Penelitian - Fauzi, Ahmad; Khafidhoh, Khafidhoh; Ahmadi, Ahmadi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This article discusses educational supervision through a comprehensive analysis of the principles of supervision derived from the Qur'an and Hadith. The study was conducted using a library research method that aims to describe the concept of educational supervision, analyze the Qur'anic basis of supervision through the concept of al-riqābah, and examine the principles of supervision taught in the Prophet's hadith which emphasize accountability and the quality of devotion in carrying out the mandate. The results of the study indicate that the Qur'an emphasizes divine supervision, the recording of angels, and self-awareness as the moral foundations in supervisory activities, while the Prophet's hadith emphasizes that every individual bears the mandate of leadership that must be accounted for and encourages optimal implementation of tasks through the value of ihsan. The integration of these two sources of Islamic teachings produces a framework for educational supervision that balances academic, spiritual, and ethical aspects so that it can be used as a guideline in developing a holistic supervision program in Islamic educational institutions.